Comparison of Accuracy of Different Generations of Apex Locators in Determining Working Length: A Systematic Review and Meta – Analysis - Nahlah khalil Alblowi , Badr Omar Al – Ahmadi , Ali Mohammed Falatah , Tariq Muteb Alharbi , Fayez Abdurrahman Aloufi , Bakr M sedqi , Suhail Abdulrahman Al - Amoudi (Migration Letters, 2022)
The aim of this study was to assess the accuracy of different generations of electronic apex locators. Methods and materials: Articles on different generations of electronic apex locators were selected from the PubMed, Cochrane Library, Google Scholar, and ScienceDirect databases using the search term apex locators. Moreover, eligibility criteria were set and used for the inclusion of articles. Results: Fifteen studies satisfied the eligibility of the criteria and were included in the study. Based on the results of four meta - analyses, the Cochran’s Q - values were 3.042, 4.569, 0.636, and 0.443. The I2 value of four heterogeneity tests was zero (I2 = 0). In addition, the risk ratios of the four meta - analyses were 1.040, 0.997, 0.935, and 0.959. Conclusions: All four generations of electronic apex locators under reviews were found to be accurate in measuring working length. Therefore, the generation of apex locators does not play a significant role in how accurately electronic devices determine working length.